Produksi Ikan Nila Dengan Teknologi Mono Kelamin dan Pakan Kombinasi Tepung Magot di Desa Tanjung Raya Kabupaten Ogan Ilir - Muslim Muslim; Danang Yonarta; Muhamad Said (Jurnal PKM Manajemen Bisnis, 2026)
Tilapia farming in rural communities often faces challenges related to low growth rates and inconsistent seed quality. To address these issues, a community service program (PKM) was implemented to introduce monosex tilapia production technology combined with maggot-meal feed as an alternative protein source. This program aimed to enhance the technical capacity of local fish farmers and improve cultivation productivity in Tanjung Raya Village, Ogan Ilir Regency. The PKM was carried out on 22 September 2025 by a team of three lecturers from Universitas Sriwijaya and involved 15 members of the Maju Makmur Fish Farmers Group. The activity followed three stages: preparation, implementation, and reporting. The implementation consisted of material presentations, hands-on practice, discussions, and question-and-answer sessions. Participants were trained on monosex tilapia seed production techniques, the use of maggot-meal combination feed, and best management practices for freshwater aquaculture. The program resulted in increased farmer knowledge, improved skills in applying monosex technology, and greater understanding of cost-efficient feed formulation. Participants expressed high enthusiasm and readiness to adopt the introduced methods in their farming operations. This PKM activity is expected to support the sustainability and productivity of tilapia aquaculture in the village.